Features of the compound ALM-802 antiarrhythmic action - V. V. Barchukov; V. P. Zinchenko; I. B. Tsorin; I. Yu. Teplov; V. N. Stolyaruk; M. B. Vititnova; G. V. Mokrov; S. A. Kryzhanovskii (Фармакокинетика и Фармакодинамика)
Introduction. Cardiovascular diseases (CVD) remain one of the leading causes of death worldwide, claiming over 17 million lives annually. This highlights the urgent need to develop innovative drugs to combat CVD. One potential target for such drugs is type 2 ryanodine receptors (RyR2), as they play an important role in maintaining ion homeostasis in cardiomyocytes, and their abnormal activity plays a key role in the genesis of cardiac arrhythmias.Research objective is to study the mechanisms underlying the antiarrhythmic action of ALM-802.Methods. In the ﬁrst stage, in vivo experiments were performed using models of aconitine, calcium chloride, barium chloride arrhythmia, and reperfusion arrhythmias to evaluate the antiarrhythmic eﬀect of the compound ALM-802. The second stage of the study involved electrophysiological experiments performed on hippocampal cells of newborn rats to evaluate the eﬀect of the compound on voltage-gated transmembrane Na+, K+, and Ca2+ ion channels, as well as its eﬀect on intracellular ion concentration of Ca2+. Experiments performed on an isolated myocardial strip evaluated the eﬀect of the compound ALM-802 on the activity of RyR2.Results. In in vivo experiments, the compound ALM-802 (2 mg/kg, iv) exhibits signiﬁcant antiarrhythmic activity comparable/superior to that shown by the reference drugs procainamide, verapamil, and amiodarone on the models mentioned above. In in vitro experiments, it was shown that ALM-802 (69.8 µM) initiates the inactivation of K+ and Na+ ion channels and does not aﬀect the activity of Ca2+ ion channels. The compound ALM-802 eﬀectively prevents the increase of Ca2+ ion concentration in the cytosol during depolarization of contraction. In addition, experiments on isolated myocardial strips showed that the compound ALM-802 (5x10-5 M) blocks RyR2.Conclusion. Thus, based on the spectrum of its antiarrhythmic activity, the compound ALM-802 combines the properties of antiarrhythmic drugs of class IA or IC and class III according to the E.M. Vaughan Williams classiﬁcation. In addition, the ALM-802 compound exhibits antagonistic activity towards RyR2. The latter is also considered signiﬁcant, as it is known that under conditions of myocardial pathology, abnormal activity of RyR2 initiates diastolic leakage of Ca2+ ions from the sarcoplasmic reticulum cysterns, which leads to a decrease in the inotropic function of the left ventricle of the heart and signiﬁcantly increases the risk of developing malignant cardiac arrhythmias.